The organophosphate chlorpyrifos disturbs redox balance and triggers antioxidant defense mechanisms in JEG-3 cells - Chiapella, Graciela (2013)
Introduction: Reactive oxygen species (ROS) are produced by a number of physiological and pathological processes which influence the function of a diverse array of cellular events. An imbalance between ROS generation and elimination was reported for different environmental xenobiotics exposure. Here, we analyzed the effect of chlorpyrifos (CPF) on the JEG-3 cell antioxidant defense in conditions where cell viability and morphology were not altered. Methods: Acetylcholinesterase (AChE) activity, reduced glutathione (GSH) content and catalase (CAT) antioxidant enzyme activity were measured by biochemical studies. ROS production was detected using the fluorogenic probe 2′,7′-dichlorodihydrofluorescein diacetate. The transcript level of superoxide dismutase enzyme 1 (SOD1), glutathione reductase (GR), heme oxygenase-1 (HO-1), and nuclear factor E2-related factor 2 (Nrf2) as well as Nrf2 protein amount were analyzed by quantitative real time PCR and Western blot, respectively. Results: The results showed that CPF inhibited AChE activity, induced ROS production, upregulated CAT activity, and decreased GSH concentration. In response to CPF exposure, GR and HO-1 mRNA levels were increased with no changes in SOD1 mRNA. Furthermore, CPF significantly augmented Nrf2 at both mRNA and protein levels trigging the antioxidant status by increasing nuclear Nrf2 translocation. Discussion and conclusion: Taken together, these data indicate that JEG-3 cells are able to attenuate the oxidative stress induced by CPF through the adaptive activation of the Nrf2/ARE pathway.